1998
DOI: 10.1097/00004032-199802000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Based Method for Conversion of In-Situ Gamma Ray Spectra Obtained with a Portable Ge Detector to an Incident Photon Flux Energy Distribution

Abstract: A Monte Carlo based method for the conversion of an in-situ gamma-ray spectrum obtained with a portable Ge detector to photon flux energy distribution is proposed. The spectrum is first stripped of the partial absorption and cosmic-ray events leaving only the events corresponding to the full absorption of a gamma ray. Applying to the resulting spectrum the full absorption efficiency curve of the detector determined by calibrated point sources and Monte Carlo simulations, the photon flux energy distribution is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
9

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 0 publications
1
15
0
9
Order By: Relevance
“…Based on the above and in particular for phosphogypsum usage as soil conditioner, GAEC has established a concentration limit for 226 Ra equal to 400 Bq/kg (GAEC's Decision 414/875/2001, 2001. For the scrap metals, the criteria used for their recycling, with no further restrictions, were based on the EC recommended radiological protection criteria for the recycling of metals from the dismantling of nuclear installations (EC Publications RP 89, 1998).…”
Section: Basic Principles and Legislationmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the above and in particular for phosphogypsum usage as soil conditioner, GAEC has established a concentration limit for 226 Ra equal to 400 Bq/kg (GAEC's Decision 414/875/2001, 2001. For the scrap metals, the criteria used for their recycling, with no further restrictions, were based on the EC recommended radiological protection criteria for the recycling of metals from the dismantling of nuclear installations (EC Publications RP 89, 1998).…”
Section: Basic Principles and Legislationmentioning
confidence: 99%
“…To be in compliance with the legislative provisions mentioned before, the dose criterion for metals recycling was converted to specific activity through dosimetric models (GAEC Sub/01/325929/2004, GAEC, 2004Clouvas et al, 1998). The scenarios took into account the entire sequence of scrap processing, starting with transport and handling of the scrap metal up to exposure from consumer goods made of recycled metal.…”
Section: Scrap Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1989, Clouvas et al [19] noted that the efficiency measurements for their detector yielded a dead layer thickness of 2.5 mm that did not agree with the value of 0.5 mm provided by the manufacturer. They additionally found that in order to model the energy spectrum from their p-type coaxial detector at low energies, they needed to include a transition layer where partial charge collection occurred.…”
Section: Introductionmentioning
confidence: 96%